IMPACT OF PERCEIVED STRESS ON GENERAL HEALTH: A STUDY ON ENGINEERING STUDENTS - Yadav, Sresha; Ghosh, Vinit; Kumar, Ishwar (PEOPLE: International Journal of Social Sciences, 2018)
In today’s competitive world, individuals have to undergo varied stressful situations right from their adolescence to old age. Students who are pursuing their higher education cannot keep themselves away from the inevitable and inescapable wrath of anxiety and stress, resultant from the demands of the present education system. Thus, the present research examines the relationship between perceived stress and general health of engineering students. The Perceived Stress Scale (PSS; Cohen et al., 1988), and the General Health Questionnaire (GHQ; Goldberg, 1981) were administered on 139 engineering students from two reputed engineering institutions in India, one in Bangalore and the other in Raipur, aged 18 to 22 years. Data analysis techniques such as Pearson correlation coefficients were used to identify relationships between perceived stress and general health. General health consists of two factors: sense of accomplishment (SOA) and botheration-free existence (BFE). Results showed that both SOA and BFE are negatively correlated with stress. As perceived stress increases, student’s sense of accomplishment (i.e. their zeal to make an impact) decreases, but this relationship was found to be non-significant. Again, stress was negatively correlated with BFE and this time a significant relationship was found, i.e. as stress increases it induces worry and botheration in students. Further, this means that in these institutions, students’ perceived stress induces negative health conditions in them. However, students who can adapt better coping mechanism would have a better state of general health.